Knowledge, Attitude and Practice of Mothers of Children Below Five Years Regarding Diarrhoea - Gupta, Dipak Kumar; Sah, Poonam Kumari (Nepal Journal of Health Sciences, 2021)
Background: The public health problem of diarrhoeal diseases is widespread. In order to reduce related mortality and morbidity, caretakers must play an active role and need to determine to what extent they are empowered. Method: A cross sectional descriptive study was conducted from March 7- April 6, 2021 among 113 mothers of children below five years who visited hospital-seeking treatment for diarrhoeal diseases of their children. A self-structured questionnaire regarding knowledge, attitude and practice regarding was used to generate data on interview basis. Results: Knowledge regarding the diarrhoeal disease was found to be of good level (88.4% correctly defining diarrhoea). Majority of mothers has good attitude towards diarrhoea. However, far few mothers correctly recognised signs of dehydration, 23 recognizing dry mucosa and 44 recognizing sunken eyes. Out of total, 81% participants knew about oral rehydrate solutions. Conclusion: Despite good knowledge and attitudes towards diarrhoea among mothers with children under five years of age, the standard of home-based management was found to be unsatisfactory based on the results of the study.